Epidemiology and Genetic Diversity of Colistin Nonsusceptible Nosocomial Acinetobacter baumannii Strains from Russia for 2013-2014 - Eugene A. Sheck; Mikhail V. Edelstein; Marina V. Sukhorukova; Natali V. Ivanchik; Elena Yu. Skleenova; Andrey V. Dekhnich; Ilya S. Azizov; Roman S. Kozlov (Canadian Journal of Infectious Diseases and Medical Microbiology)
A high level of resistance to carbapenems in Acinetobacter baumannii strains severely limits therapeutic possibilities. Colistin is the last resort drug against such strains, although the cases of resistance to this drug have become more frequent. This article presents the epidemiological features and genetic diversity of colistin nonsusceptible A. baumannii strains collected as part of a national multicenter epidemiological study of the antibiotic resistance of pathogens of nosocomial infections (MARATHON), which was conducted in 2013-2014 in Russia. A total of 527 A. baumannii isolates were collected, 10 (1.9%) of which were nonsusceptible to colistin. The majority of nonsusceptible A. baumannii isolates to colistin showed resistance to carbapenems and had the genes of the acquired OXA-40-like carbapenemases (n=6). In one case, a combination of OXA-23-like + OXA-40-like (n=1) genes was identified. One strain had the multidrug-resistant (MDR) phenotype, 6 isolates had extensively drug-resistant (XDR) phenotype, and 3 isolates had pandrug-resistant (PDR) phenotype. Among the colistin nonsusceptible A. baumannii isolates, 6 individual genotypes were identified, most of which belonged to successful international clones (CC92OXF/CC2PAS, n=4; CC944OXF/ST78PAS, n=4; CC109OXF/CC1PAS, n=1).